Copper (I)-Chloroquine Complexes: Interactions with DNA and Ferriprotoporphyrin, Inhibition of β-Hematin Formation and Relation to Antimalarial Activity - Wilmer Villarreal; William Castro; Sorenlis González; Marylin Madamet; Rémy Amalvict; Bruno Pradines; Maribel Navarro (Pharmaceuticals, 2022)
A new Cu(I)-chloroquine (CQ) complex [Cu(CQ)(PPh3)2]NO3 (1) was synthesized and characterized, and its mechanism of action studied concomitant with the previously reported complex [Cu(CQ)2]Cl (2). These copper (I) coordination compounds can be considered as potential antimalarial agents because they show better inhibition of the CQ-resistant strain in in vitro studies than CQ alone. In comparison with other metal-CQ complexes, only the gold complex was similar to (1), i.e., more active than CQ against both CQ-susceptible (3D7) and CQ-resistant strains (W2). These two copper (I)-compounds also demonstrated higher antiplasmodial activity against W2 than other copper complexes reported to date. This suggests that the incorporation of the copper metal center enhanced the biological activity of CQ. To better understand their significant growth inhibition of the Plasmodium falciparum parasite, the interaction with two essential molecular targets for the survival and proliferation of the malarial parasite were studied. These were the ferriprotoporphyrin group and the DNA, both important targets for current antimalarial drugs at the asexual erythrocytic stages. Both compounds (1,2) exhibited significant interactions with these targets. In particular, interactions with the DNA were dominated by the intercalator properties of the CQ ligand but may have also been affected by the presence of copper. Overall, these compounds were better parasitic inhibitors than chloroquine diphosphate (CQDP) alone or other previously reported metal-CQ complexes such as platinum, ruthenium and gold.